Shock - Cook, Robin, 1940- (New York : Putnam's, 2001)
To earn some extra money, Deborah Cochrane and Joanna Meissner, two financially strapped graduate students, become involved with a Boston fertility clinic in search of egg donors, but they become suspicious about the clinic and its head, Dr. Spencer Windgate, and risk their lives to uncover the truth.
Keywords: Cloning -- Fiction; Medical novels